Reading Challenges in Elementary School Students' English as a Foreign Language - Suryantini, Made Detri; Dewi, Ni Putu Artila; Sintadewi, Ni Made Dita (Jurnal Basicedu, 2024)
This study looked into the types of comprehension-related reading issues that fourth-grade kids faced, the factors that influence reading difficulties, and the efforts made by these students, who were between the ages of 11 and 12, to overcome their reading difficulties. The study used a qualitative method to try to understand the reading challenges of English as a foreign language. Twenty-two fourth-graders served as the research subjects. Questionnaires, documentation, and interviews were employed in the data collection process. Qualitative data analysis was the method employed. The study's findings showed that 15 students had trouble reading and that they had trouble understanding English reading texts when they were given by their teachers. Fourth-grade pupils' difficulties reading English was caused by an internal factor: they were less motivated to learn English in class and had a smaller vocabulary. Regarding the external component, the school library contained no references to English-reading books. It is evident from the previous results that fourth-grade elementary school kids struggle with reading.